Stepfamily Break-Up: A Qualitative Analysis of Trajectories and Processes. Issue 8 (16th November 2016) - Saint-Jacques, Marie-Christine; Godbout, Elisabeth; Gherghel, Ana; Parent, Claudine; Drapeau, Sylvie; Robitaille, Caroline
ABSTRACT: Stepfamilies are considered to be less stable than first unions. There has been little research conducted that explains why stepfamilies break up or what the viewpoint of the parents and stepparents is. This qualitative study, which was based on life course theory, analyzed the statements made during an interview of 26 parents and stepparents who separated in the first 5 years of their relationship. The results showed that the underlying elements of the separation could be understood by way of past experiences, models, and values acquired during childhood and in previous conjugal relationships. During the stepfamily period, significant events and differences in the partner's life stages pushed their trajectory from one of stepfamily creation to separation. An analysis of the mechanisms that were set in motion after these events revealed the processes to be integrated in the prevention of conjugal and family difficulties.